Ethics within chemistry education: options, challenges and perspectives - Mammino Liliana (Chemistry Teacher International)
Ethics considerations are necessary in all human activities. They are particularly important for activities that impact on human wellbeing and society. Chemistry has paramount impacts because of the extensive presence of chemistry-based items in everyday life and their eventual impacts on the environment, which, in turn, affect human beings because humans live in the environment and depend on it. Therefore, it is important to include ethics considerations in chemistry education at all levels and – to a larger extent – in the preparation of chemistry specialists. The present work analyses the main challenges associated with the incorporation of ethics into chemistry courses, and outlines possible promising approaches. When considering chemicals, the major ethical-type terms could be the benefits from their use and the possible harms to human beings or the environment: therefore, the “doing good” ethical concept can be associated with maximising the former and minimising the latter. The ways in which benefits or harms occur can be analysed in terms of the nature of selected chemicals, their usage modes, the routes through which they may enter the environment, and the undesirable effects they may cause through inappropriate usage or through their presence in the environment.